COMPARATIVE ANALYSIS ON THE VALIDITY OF NOMINEE AGREEMENT ON THE OWNERSHIP OF SHARES BETWEEN INDONESIA AND SINGAPORE - Ricky, Claudio; Sugianto, Fajar; Maretta, Yohanie (International Journal of Law in Changing World, 2024)
Share ownership as a form of investment is regulated by laws that protect companies and their shareholders. In addition to these laws and regulations, shareholder agreements and the Civil Code safeguard the interests of shareholders and the company. Nonetheless, legal circumvention often occurs due to investment restrictions, such as the widespread practice of Nominee Agreements. However, some of these regulations confuse the nominee and the Beneficial Owner (BO), allowing for abuse and violation of the law. This research focuses on the concept of nominee shareholding agreement in Indonesia and its comparison with Singapore, using the theories and concepts of comparative law, legal entity, corporate organ, agreement, share, shareholder, beneficial owner, and legal principles approach to show that Indonesia rejects and prohibits nominee agreements, while Singapore protects certain conditions for nominee shareholders and nominee directors who meet their requirements. This difference in approach is reflected in the legal consequences given to parties who violate these regulations in each country. __________ La propiedad de acciones como forma de inversión está regulada por leyes que protegen a las empresas y a sus accionistas. Además de estas leyes y regulaciones, los acuerdos entre accionistas y el Código Civil salvaguardan los intereses de los accionistas y de la empresa. No obstante, a menudo ocurre la evasión legal debido a restricciones de inversión, como la práctica generalizada de los acuerdos de nominados. Sin embargo, algunas de estas regulaciones confunden al nominado con el Propietario Beneficiario (Beneficial Owner, BO), lo que permite abusos y violaciones de la ley. Esta investigación se centra en el concepto de acuerdos de propiedad de acciones mediante nominados en Indonesia y su comparación con Singapur, utilizando teorías y conceptos de derecho comparado, entidad jurídica, órgano corporativo, acuerdo, acciones, accionista, propietario beneficiario y enfoques basados en principios legales. Se demuestra que Indonesia rechaza y prohíbe los acuerdos de nominados, mientras que Singapur protege ciertas condiciones para accionistas nominados y directores nominados que cumplen con sus requisitos. Esta diferencia de enfoque se refleja en las consecuencias legales aplicadas a las partes que violan estas regulaciones en cada país. __________ 作为一种投资形式，股份所有权受到法律法规的保护，这些法规旨在保护公司及其股东。除了这些法律和法规，股东协议和民法典也保障了股东和公司的利益。然而，由于投资限制，法律规避现象经常发生，例如提名协议的广泛实践。然而，这些规定中的某些内容将提名人和实益所有人（Beneficial Owner, BO）混淆，从而导致滥用和违法行为。本研究重点探讨印尼的股份提名协议概念及其与新加坡的比较，采用比较法、法人实体、公司机关、协议、股份、股东、实益所有人及法律原则的理论和概念方法。研究表明，印尼拒绝并禁止提名协议，而新加坡在特定条件下保护符合要求的提名股东和提名董事。这种差异反映在两国对违反这些规定的当事人所施加的法律后果中。